A comparison of personal preferences of the second generation returnees and their peers raised in Turkey - İnceoğlu, Derya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1985., 1985)
The present exploratory and descriptive study investigated the personality variables and preferences of the returnees who are at the adolescent period. The hypothesis was that the returnee youth show differences compared to the youth who were raised in Turkey in terms of personal preferences and personality variables. There were three comparison groups which included 240 high sohool lycee one level students from three different lycee in istanbul. Eighty of the subjects were second generation returnees from The Üsküdar Anadolu Lycee eighty from another anadolu lycee and eighty from a regular lycee. The main instrument was the EPPS (Edwards' Personal Preference Schedule). A demographic 1.1 information questionaire was also given to the sample group. The two way analysis of variance wus used to analyze the data. The results did not support the hypothesis for 14 of the EPPS variables and only on the preference for Nurturance did the returnee group seperated itself from the Turkish raised youth.
Keywords: Children of immigrants.; Choice (Psychology); Edwards personal preference schedule.; Personality tests.